PEMBELAJARAN MEWARNAI GAMBAR UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS PADA ANAK USIA 5-6 TAHUN - Meylinie, Nieta; Astuti, Indri; Marmawi, Marmawi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractÂ The purpose of this research is to describe 1) learning plan of coloring drawing to improve the fine motor ability of the child, 2) Implementation of learning coloring drawing to improve the fine motor ability of the child, and 3) Improvement of color picture learning to improve fine motor ability of child. Researchers used the method of descriptive. The form of this research is classroom action research. The conclusions show: 1) Learning planning coloring the image to improve the fine motor ability of the child, has been in accordance with the steps that have been determined with the category not implemented in cycle 1 and on the second cycle with the category performed well, 2) Implementation of the learning coloring drawing to improve fine motor skills of children, has been implemented by the teacher well, because the teacher performs in accordance with the planning made, both in cycle I and in cycle II, and 3) Improvement of color picture learning to improve the fine motor skills of children, in cycle I get the average value 49,4 which categorized not good, while in cycle II very good increase with value 98,2. Keywords: Coloring pictures, fine motor skills